Using Dynamic Stability Strategy to Counteract Rapid Changing Demand Considering Deterioration and Partial Backordering - Yu, J.C.P.; Lin, X. B.; Chen, J.M. (ExcelingTech, 2024)
In a real business world, the production plan must respond to quick changing market and keep production line stable. An optimal stepwise production strategy is derived with stable production rate for some period, and then changing to another stable production rate to response market change for the next period. The cost factors we considered in the model include the production setup cost, the production-variation cost, the carrying cost, the deteriorating cost, the backordering and the lost sale shortage cost. For demand that changes linearly or exponentially with time, an inventory model with partial backordering is developed. Finally, sensitivity analysis is carried out to investigate how changing parameters affect this system.